Social reinsertion of former detainees: Between perception and attitude - Sandu, Mihaela; Calin, Mariana Floricica; Constantin, Marius (Technium Social Sciences Journal, 2021)
It is known that at the level of each society there are manifestations of violation of the rules, the rules that can take the form of deviance. Individuals who violate these rules, legally commit crimes. Successful crime prevention strategies must address the factors that contribute to the large number of crimes committed by individuals who have served a term of imprisonment and have failed, after release, to integrate into the community as law-abiding citizens. I chose to carry out this research because the community, the society belongs to everyone, therefore both I and my family, friends and relatives are directly affected by the present criminal phenomenon. The aim of the paper is to raise public awareness about the situation of those who have been deprived of their liberty in their quest to be among us again, how we can help them and implicitly us, in this difficult process of social reintegration. Awareness of the perception of the population regarding the reintegration of former detainees, of the difficulties encountered by them in trying to return to a fair life is a significant element in forming / changing attitudes towards them, a reintegrated person, a gain for the community. We do not live alone, isolated, therefore thousands of people released from prisons in just a few months live among us trying to survive in an environment often hostile so that there are many cases in which they relapse involving high costs both financial and psychosocial for the belonging community. The research was conducted in a difficult time for the whole world, when tens of thousands of people lost their jobs and socialization was drastically reduced with still uncertain prospects for the future but people were open to answering questions even if they themselves need social reintegration, although they have not served a legal sentence of deprivation of liberty. However, this pandemic context has brought a global awareness of the effects of deprivation of liberty, with psychological effects being present in a significant proportion of a large part of the population.